الإطار النظري للسرقة العلمية - لكموته إبراهيم; لبزة هشام; زين يونس (University Of Eloued جامعة الوادي, 2023)
Scientific research in the various sciences is considered the basic pillar upon which university studies are based; it has great importance in acquiring knowledge and trying to scrutinize and develop it, and for academic scientific research to achieve its goal, it has become necessary to have basic criteria for it to be considered, because departing from these accepted norms It is considered a violation of what is required by law in preparing scientific research. In this study, we will look at the phenomenon of scientific theft, as it is the most serious violations that the researcher may have occurred, which has exploded in the Algeria university circles in a large way recently, as it has become a real threat to the credibility of the Algerian scientific research in light of its appearance in multiple forms of varying severity, despite It is one of the preventive and punitive efforts that Algeria seeks to activate in combating scientific theft but it did not achieve the desired results, and it did not contribute sufficiently to protect intellectual production
Scientific theft
مداخلة
Keywords: الإنتاج العلمي; البحث العلمي; الباحث; الدراسات الجامعية; السرقة العلمية; الجهود الوقائية; الجهود العقابية; scientific production; Research; researcher; University studies; academic plagiarism; Preventive efforts; punitive efforts